Using bioinformatic tools in exploited gene encoding enzyme to decompose lignocellulose from metagenome of free - living bacteria in the gut of the lower termite Coptotermes gestroi - Giang, Nguyễn Minh; Huyền, Đỗ Thị; Hải, Trương Nam (Vietnam Journal of Biotechnology, 2016)
Microbial metagenome DNA in the guts of Coptotermes gestroi has been extracted and sequenced by metagenomic techniques. In previous studies, we acquired and sequenced more than 5 Gb of DNA metagenome DNA of the termite gut microbiota by next-generation sequencing (Illumina). Software MGA (MetaGeneAnnotator) exploited 125.431 open reading frames with 8508 ORFs related to carbohydrate metabolism, including 587 ORFs coding for enzymes involved in the hydrolysis of lignocellulose. We identified software to reliably predict function, structure and characteristics of proteins corresponding to DNA sequences encoding alkaline enzymes from the metgenome of C gestroi. The online software Alcapred was used to predict alkaline enzymes, Blastp to predict conserved domains of amino acid sequences deduced from ORFs, Phyre2 to predict the three dimentional structure and substrate binding site of the enzymes, TBI to predict melting temperature of the enzyme. We identified 6 ORFs encoding alkaline cellulases (GL0101308, GL0038126) or alkaline hemicellulases (GL0120095, GL0074258, GL0112518, GL0067868). The amino acid sequences deduced from ORFs had 90% coverage and from 44% to 99% identity to the corresponding sequences in NCBI by BLASTP. All of them contained conserved domains with corresponding activities and binding sites of the enzyme to the substrate. The three dimentional structures of amino acid sequences were predicted by Phyre2 with reliability from 98% to 100% to the annotated activities. Among six selected amino acid sequences, two sequences of enzymes had the melting temperature above 65 ℃, three sequences had melting temperature from 55℃ to 65℃ and only one below 55℃.